2009
DOI: 10.1074/jbc.m805570200
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Role of p53 in Hyperpigmentation of the Skin via Regulation of Paracrine Melanogenic Cytokine Receptor Signaling

Abstract: Hyperpigmentation of the skin is characterized by increases in melanin synthesis and deposition. Although considered a significant psychosocial distress, little is known about the detailed mechanisms of hyperpigmentation. Recently, the tumor suppressor protein p53 has been demonstrated to promote ultraviolet B-induced skin pigmentation by stimulating the transcription of a melanogenic cytokine, POMC (pro-opiomelanocortin), in keratinocytes. Given that p53 can be activated by various kinds of diverse stresses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 76 publications
6
75
0
1
Order By: Relevance
“…Additionally, it was also confirmed that cell viability was not changed by the application of this extract to HSSs (data not shown). This inhibitory effect on melanin synthesis in HSSs was shown to be equal to that of pifithrin-α, the inhibitor of SCF-inducing phosphorylation of MAPK, as we previously reported [8]. Additionally, our clinical study revealed that application of this extract significantly depresses UVB-induced pigmentation even at 1 week after irradiation in a dose-dependent manner (Fig.…”
Section: Resultssupporting
confidence: 84%
“…Additionally, it was also confirmed that cell viability was not changed by the application of this extract to HSSs (data not shown). This inhibitory effect on melanin synthesis in HSSs was shown to be equal to that of pifithrin-α, the inhibitor of SCF-inducing phosphorylation of MAPK, as we previously reported [8]. Additionally, our clinical study revealed that application of this extract significantly depresses UVB-induced pigmentation even at 1 week after irradiation in a dose-dependent manner (Fig.…”
Section: Resultssupporting
confidence: 84%
“…The transcriptional activation of KITLG upon p53 activation has been clearly demonstrated in multiple studies utilizing different cell types, different p53-activating stimuli and different measurement techniques (McGowan et al, 2008; Murase et al, 2009; Smeenk et al, 2011; Terzian et al, 2010; Wei et al, 2006). Consistent with this, we observed significant p53 binding to KITLG in the region that harbors the KITLG p53-RE SNP, in 10 out of 11 different cell line and treatment combinations (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, KITLG and its receptor C-KIT are a part of a pathway that is known to be central in regulating proliferation, survival and migration of primordial germ cells, melanoblasts and hematopoietic stem cells (Lennartsson and Rönnstrand, 2012). In the pigmentary system, ultraviolet radiation induces p53-Kitlg signaling in keratinocytes, which in turn affects melanocytes that express the c-Kit receptor in order to mount a cutaneous UV response such as tanning (Murase et al, 2009). Interestingly, when we compared this response in mice either wild-type (WT) or null for p53 ( p53 null ), we noted dramatic differences.…”
Section: Resultsmentioning
confidence: 99%
“…Our results unraveled a mechanism involving a-MSH and p53 in the adaptive response of melanocytes to UVR. Others have shown that p53 increases the expression of the melanogenic enzymes tyrosinase and tyrosine-related protein 1 (TYRP-1), suggesting its role in regulating melanogenesis (20,21). In mouse skin, p53 stimulates the expression of proopiomelanocortin (POMC), the precursor of a-MSH and adrenocorticotropic hormone (ACTH; refs.…”
Section: Introductionmentioning
confidence: 99%